A case study on thermal comfort in maternity hospital in Beijing - DU, Bo-Yu (2018)
Thermal comfort is a vital evaluation of indoor thermal comfort, which is widely applied in economic building, office building and school building etc. Compared to previous investigations in general hospital, only a few studies focused on maternity hospital. In this research, thermal comfort in a maternity hospital was investigated whether there was a comfort environment for pregnant women’s delivery, visitors’ accompany and staff’s working. In order to ensure the measurements are scientific and suitable, both foreign and domestic researches were referred in terms of thermal comfort in hospital. Both objective and subjective measurements were conducted in a maternity hospital in transition season ranging from March to April in Beijing. The objective measurements such as air temperature, relative humidity, air velocity and carbon dioxide were recorded by equipment placed in one ward, one doctor’s office and one nurse station, respectively. The subjective measurements included personal clothing insulation, activity levels, thermal sensation, thermal expectation, humidity sensation and other sensibility related to environments were collected by 168 effective questionnaires. The linear regressions were applied to compare the relationship between the thermal sensation and environmental parameters and personal factors. The result showed that a) Indoor temperature and humidity basically met the requirements of domestic standard, which were 24.52-26.91℃ and 24.29-28.84℃ in March and in April, respectively; the relative humidity was ranged from 25.44-42.40% and 32.66-64.00% in March and in April, respectively. b) There was no difference between subjective and objective thermal sensation values, p=0.101, however, the average value of objective was higher 1.57 than that of subjective, which indicated that people felt warmer than PMV predicted sensation. c) Individual’s actual thermal sensation was various in different months which individual would feel warmer in the basically same indoor temperature in ventilation season than heating season.